The development of medical tourism in Malaysia: factors, actors, and strategies / Nur Alia Azmi - Azmi, Nur Alia (2020)
Medical tourism is defined as a movement of people from one country to another to receive medical treatment as well as to enjoy site tourism attractions. Medical tourism industry in Malaysia was introduced in 1998. The industry is growing fast that it has generated a profit of MYR 1.5 billion and the number of medical tourists 25.8 million in 2018. Currently, Malaysia has become one of the best countries in the Southeast Asia region (SEA) in the health tourism industry and is competing with developed countries such as United States, United Kingdom, Costa Rica, Japan, Brazil and Singapore. Based on recent statistics, Malaysia is on her way to be the best medical tourism hub in SEA region, yet literatures need to be update on the factors, who are the main actors behind the rising of medical tourism and the challenges they face as well as the feasible strategies undertaken by the government and relevant parties to promote the industry. Hence, the purpose of this study is to explore the development of medical tourism in Malaysia through three core elements namely factors, actors, and current strategies that lead to the development of Malaysia's medical tourism. This research has applied qualitative method. In-depth interviews were conducted with eighteen (18) informants from the government ministries, agencies and private hospitals in Selangor and Kuala Lumpur. Content analysis through government reports on medical tourism were also analyzed. The data collected from the interview were scrutinized through thematic analysis. The findings are as follows: (1) factors that made Malaysia a preferred medical tourism destination are: high quality services, affordable cost, site attraction places, Syariah medical practices, government initiatives and smart partnerships. (2) The key actors that drives the medical tourism industry are: government ministries and agencies, and the private hospitals and finally (3) the government has implemented two major strategies to promote the industry, namely smart partnerships and to increase quality healthcare services. The findings contribute significantly towards literature in the field of study and these findings can help relevant agencies to develop various strategies to promote and improve the industry.